Brain activation during music listening in individuals with or without prior music training - Seung, Yunhee; Kyong, Jeong-Sug; Woo, Sung-Ho; Lee, Byeong-Taek; Lee, Kyoung-Min (Neuroscience research, 2005)
The present study investigated activation during listening to music with and without a task in female musicians and non-musicians. Five subjects with long musical training for a mean period of 19 ± 1 years (musician group) and five subjects with no training in musical instruments (non-musician group) were imaged in a 1.5 T scanner, while they simply listened to short segments of piano pieces (LIS), and while they performed a distorted tune test, designed using the same pieces (DTT). A significant group effect with higher signals in the musician group was observed in the right superior and middle temporal gyri, the right inferior frontal gyrus, and the left supramarginal gyrus. A task effect with higher signals during DTT was observed in the left sensorimotor cortex, where the interaction between the task and group effects was also significant. Thus, the pattern of brain activation differed depending on tasks when identical music stimuli were used, and more importantly, comparable music tasks activated the brain differently depending on prior musical training of subjects.